Clearance of refractory bile duct stones with extracorporeal shockwave lithotripsy. Issue 5 (1st November 2000) - Ellis, R D; Jenkins, A P; Thompson, R P H; Ede, R J
Abstract : BACKGROUND: Extracorporeal shockwave lithotripsy (ESWL) has been used since the mid-1980s to fragment bile duct stones which cannot be removed endoscopically. Early machines required general anaesthesia and immersion in a waterbath. AIMS: To investigate the effectiveness of the third generation Storz Modulith SL20 lithotriptor in fragmenting bile duct stones that could not be cleared by mechanical lithotripsy. METHODS: Eighty three patients with retained bile duct stones were treated. All patients received intravenous benzodiazepine sedation and pethidine analgesia. Stones were targeted by fluoroscopy following injection of contrast via a nasobiliary drain or T tube. Residual fragments were cleared at endoscopic retrograde cholangiopancreatography. RESULTS: Complete stone clearance was achieved in 69 (83%) patients and in 18 of 24 patients (75%) who required more than one ESWL treatment. Stone clearance was achieved in all nine patients (100%) with intrahepatic stones and also in nine patients (100%) referred following surgical exploration of the bile duct. Complications included six cases of cholangitis and one perinephric haematoma which resolved spontaneously. CONCLUSION: Using the Storz Modulith, 83% of refractory bile duct calculi were cleared with a low rate of complications. These results confirm that ESWL is an excellent alternative to surgery in those patients in whom endoscopic techniques have failed.